Les sujets-textes d’examen en breton. Présentation et analyse exploratoire d’un corpus textuel d’évaluation en langue bretonne - Fabrice David (La Bretagne Linguistique)
A great deal of attention is paid to the positioning and knowledge of learners' level of mastery of the Breton language, but this is not accompanied by consideration of the materials and tools used to assess language skills. What texts are used in Breton exams and competitions? How are they chosen? How do they relate to written production in Breton? To answer these questions, I have compiled a corpus of Breton examination subject texts from recent sessions of the baccalauréat and the CRPE. After defining the purpose of the study and explaining how the corpus was put together, this contribution maps out the subject texts and offers an initial quantitative and methodological analysis.